The driving forces of marital dissolution in Asian countries: A systematic review of literatures - Subarimaniam, Neerushah; Hassan, Siti Aishah; Zakaria, Noor Syamilah (SAGE Journals, 2017)
Marital dissolution is the legal termination of marital obligations between spouses, and it has been perceived as a very common issue, especially when there are more challenges and expectations in one’s life. This article is a systematic review study, which explores the factors or driving forces that lead to marital dissolution. Besides that, the pattern of this study is derived from a combination of marital dissolution culture, factors of marital dissolution, perspectives, and information extracted from Asian countries. Electronic database was used to search appropriate reading materials and a total of 10 journals were found. This article presents a systematic review of 10 journals that are the results of some inclusion and exclusion criteria. The driving forces of marital dissolution such as domestic violence, cohabitation, interparental conflict, economic considerations, house holding, and separation across borders were discussed systematically.